Pengaruh rasio Net Intersest Margin (NIM), Loan To Deposit Ratio (LDR) dan Non Perfoming Loan (NPL) terhadap profitabilitas bank - Hilmy Tsany, Muhammad; Bagana, Batara Daniel (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The banking industry is an important sector in national development that functions as a financial intermediary. Banks as intermediary institutions must have good performance by maintaining and improving bank soundness. Thus, banks can more easily gain and maintain the trust of their customers (agent of trust), which is a bank's fundamental principle. This study aims to examine and analyze the effect of the ratio of NIM, LDR, and NPL on Bank Profitability. The population used in this study are banking companies listed on the Indonesia Stock Exchange in 2017-2021 with a final sample of 50. The sample method used in this study is multiple linear regression analysis using the IBM SPSS 22 program. The conclusion of this study is the simultaneous variable ratio NIM, LDR, and NPL have an influence on profitability. Meanwhile, partially the ratio of NIM and NPL has no effect on profitability, LDR has a positive effect on profitability.